Mechanisms of 1s Double-Core-Hole Excitation and Decay in Neon - Maksim D. Kiselev; Elena V. Gryzlova; Sergei M. Burkov; Oleg Zatsarinny; Alexei N. Grum-Grzhimailo (Atoms, 2021)
The formation and decay of double-core-hole (DCH) states of the neon ion irradiated by an intense electromagnetic x-ray field are studied theoretically. In the present research DCH formation is the result of sequential absorption of two photons with the creation of an intermediate ion. Detailed calculations of the partial decays and probabilities of shake-ups at the atomic and ionic ionization stages are presented. The angular distribution of photoelectrons corresponding to various residual ionic states are calculated. Specifically, we predict the lack of any photoelectrons corresponding to the residual ionic state <semantics>1s12s22pnmpn′<mspace width="0.166667em"></mspace>2Sf+1D</semantics> in the direction of the electric field polarization. Dynamical competition between single-core-hole state decay and excitation is analyzed and pulse parameters corresponding to various dynamical regimes are found.